Lesser cornstalk borer monitoring with the use of pheromone traps, Elasmopalpus lignosellus (ZELLER) (Lepidoptera: Pyralidae). - Loera, Jesús; Lynch, Robert; Rodríguez, Raúl (Agronomía Mesoamericana, 2016)
Pheromone traps were used to monitor adult populations of the lesser cornstalk borer (Elasmopalpus lignosellus (Zeller) in beans (Phaseolus vulgaris L.) near Rio Bravo, Tamaulipas, Mexico. Pherocon 1C traps baited with 10 micrograms of lesser cornstalk borer pheromone in rubber septa were mast effective when placed at 0.5 m high above the ground. Traps setting in the field, along the border of the field, within the row, or across rows produced comparable captures of adult males. Pie plate sticky traps were more effective than pherocon 1C traps at 0.5 m. These two types of traps captured similar quantities of males at 1.0, 1.5, and 2.0 m heights. The feasibility of using these traps for monitoring' lesser cornstalk borer adults along the bean growing season is discussed.